PEMENUHAN AKSESIBILITAS HAK POLITIK BAGI PENYANDANG DISABILITAS PADA SAAT PEMILIHAN KEPALA DAERAH GUBERNUR DAN WAKIL GUBERNUR JAWA TENGAH TAHUN 2018 DI KECAMATAN SIDOHARJO KABUPATEN WONOGIRI - Maulia Pangestu Putri; Triyanto Triyanto; Rima Vien Permata Hartanto (Program Studi Pendidikan Pancasila dan Kewarganegaraan FKIP Universitas Sebelas Maret, 2019)
The purpose of this research is to (1) Find out the fulfillment of accessibility of political rights for persons with disabilities in Sidoharjo District Wonogiri Regency during the regional elections of Governor and Deputy Governor of central Java 2018 and (2)find out what are the supporting and inhibiting factors in fulfilling the accessibility of political rights for persons with disabilities in Sidoharjo District Wonogiri Regency during the regional elections of the Governor and Deputy Governor of Central Java 2018. This research uses a descriptive qualitative method which tends towards the ex-post facto. The sampling technique used in this research is purposive sampling with data collection techniques are interview and document analysis. The validity of the data obtained by data triangulation techniques and triangulation methods. Analysis of the data used in this study is the interactive analysis of data collection, data reduction, data presentation, and conclusion drawing. The result of the research showed that (1) fulfilling the accessibility of political rights for persons with disabilities in the 2018 regional elections was seen from the aspect of procedures, facilities, and assistive devices that were adjusted to UU No 8 of 2016 Concerning Persons with Disabilities Clause 77 point c, (2) There is a supportive and obstructive factors which are from PPK as organizer of regional elections activities and persons with disabilities. Factors supporting that come from PPK is PPK has paid attention to the accessibility of political rights for persons with disabilities in accordance with the guidelines for the June 27 2018 regional elections guidebook issued by the KPUD Wonogiri, then supporting factors that come from persons with disabilities are having their own awareness to participate in a series of regional elections activities. The obstructive factors derived from PPK is lack of understanding by the organizing committee on disability issues has caused unevenness accessibility of political rights for persons with disabilities in each TPS, then obstructive factor of persons with disabilities is the self-confidence that is embedded in oneself so that it inhibits persons with disabilities from participating in the 2018 regional elections. Keywords: accessibility, political rights, persons with disabilities